WOMEN EMPOWERMENT AND DR. B.R. AMBEDKAR’S VISION: A SOCIAL WORK ANALYSIS - Lucy; Chand, Gian; Lal, Sohan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Dr. B.R. Ambedkar is widely regarded as a fighter for the dignity of women and the champion of human rights. As a pioneering advocate for social justice, he dedicated much of his life to the empowerment of marginalized groups, particularly women and the depressed classes. His core belief was that everyone should be treated equally, regardless of caste, creed, gender, or religion. This commitment to equality led him to focus on the liberation of women and their rights, as he recognized the pervasive gender inequality within Indian society. The main objectives of the present study are to examine the role of Ambedkar’s Vision on Women Empowerment, implementation of Constitutional Provisions for Women Empowerment and to explore the scope of Social Work Practice for Women Empowerment. Researcher has applied descriptive-cum-diagnostic research design to the present qualitative and quantitative research work. Author has used primary data, which is collected from the five villages of Sonepat District from 100 respondents through random sampling and secondary data is also taken from various online and offline sources. The main findings of the study are that the key contributions of Dr. Ambedkar’s to women’s empowerment were his role in shaping the Indian Constitution. The paper focuses on Dr. Ambedkar’s thoughts and perceptions regarding women’s empowerment, highlighting his understanding of the importance of gender equality for a just and progressive society. It also examines his contributions as a thinker and social reformer, particularly in the emancipation of women and the transformation of their social status. It was concluded that B. A. Ambedkar’s contribution has a significant relevance in social work practice to work on women empowerment in the society.